Digital democracy - Sebastian Berg; Jeanette Hofmann (Internet Policy Review, 2021)
For contemporary societies, digital democracy provides a key concept that denotes, in our understanding, the relationship between collective self-government and mediating digital infrastructures. New forms of digital engagement that go hand in hand with organisational reforms are re-intermediating established democratic settings in open-ended ways that defy linear narratives of demise or renewal. As a first approach, we trace the history of digital democracy against the background of its specific media constellations, describing continuities and discontinuities in the interplay of technological change and aspirations for democratisation. Thereafter, we critically review theoretical premises concerning the role of technology and how they vary in the way the concept of digital democracy is deployed. In four domains, we show the contingent political conditions under which the relationship between forms of democratic self-determination and its mediating digital infrastructures evolve. One lesson to learn from these four domains is that democratic self-governance is a profoundly mediated project whose institutions and practices are constantly in flux.
Keywords: 300; Democratisation; Public space; Participation